2017
DOI: 10.1021/acsmedchemlett.7b00007
|View full text |Cite
|
Sign up to set email alerts
|

Development of Quinazoline/Pyrimidine-2,4(1H,3H)-diones as Agonists of Cannabinoid Receptor Type 2

Abstract: Starting from a prototypical structure , we describe our efforts to design and obtain novel quinazoline/pyrimidine-2,4(1,3)-diones with high CB2 agonist potency and selectivity as well as improved physicochemical characteristics, mainly hydrophilicity. The most potent and selective CB2 agonists, and, in this series were also endowed with lower logP values than that of GW842166X and lead compound . These derivatives appear to be promising lead compounds for the development of future CB2 agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Specific targets include sirtuins, β-secretase, hepatitis C virus (NS5B polymerase), B-Raf, phosphoinositide3-kinase (PI3K), and poly­(ADP-ribose) glycohydrolase (PARG) (Figure ). Synthetic methods to achieve quinazoline structures include starting from isatoic anhydride and cyclization of anthranilic acid using chloroformate, phosgene, , CDI, phosphoradiate, or isocyanate, or urea at high temperatures . It can also be achieved by N3 alkylation of quinazolinone using halo-anilines, triflate, thionitrile, or boronic acid .…”
Section: Introductionmentioning
confidence: 99%
“…Specific targets include sirtuins, β-secretase, hepatitis C virus (NS5B polymerase), B-Raf, phosphoinositide3-kinase (PI3K), and poly­(ADP-ribose) glycohydrolase (PARG) (Figure ). Synthetic methods to achieve quinazoline structures include starting from isatoic anhydride and cyclization of anthranilic acid using chloroformate, phosgene, , CDI, phosphoradiate, or isocyanate, or urea at high temperatures . It can also be achieved by N3 alkylation of quinazolinone using halo-anilines, triflate, thionitrile, or boronic acid .…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, the enamine linker of the lead compound was replaced by an acetamide group with the aim of decreasing lipophilicity and solving the problem of stereoisomerism.S ubsequently,t he n-pentyl chain was retained at the N1 positiono f the heterocycle, and different aliphatic substituents in the amide moiety were selected from ac ombination of structureactivity relationship (SAR) studies of previously reported quinazoline-2,4(1H,3H)-dione derivatives. The cell-based calcium mobilization assay, [28] which is ah ighly sensitivea nd easy-tohandle methodt hat has been validated with several standard cannabinoids, such as CB 2 Ra gonistJ WH-133, CB 1 Ra nd CB 2 R agonistW IN55212-2,C B 1 Ra nd CB 2 Ra gonistC P55940, CB 1 Ra ntagonist AM251, and CB 2 Ra ntagonist AM630, [29] wasu sed to evaluatei nv itro functional activities of all of these newly synthesized compounds. The bioactivity assays indicated that most of the synthesized compounds were potent CB 2 Rl igands, and some compounds exhibited highera gonist activities than GW842166X and compound 1.M oreover,i tw as shown that the functionality of these ligands was controlled by the nature of the heteroaryl functionality condensed with the pyrimidine ring.…”
Section: Introductionmentioning
confidence: 99%